Optimizing Supplier Selection in Indonesia Through Analytical Hierarchy Process (AHP): Mengoptimalkan Pemilihan Pemasok di Indonesia Melalui Proses Hirarki Analitik (AHP) - Latif, Mochamad Iqbal; Wahyuning, Hana Catur (Universitas Muhammadiyah Sidoarjo, 2024)
This study introduces a structured multi-criteria decision-making framework using the Analytical Hierarchy Process (AHP), applied to evaluate suppliers based on quality, price, quantity of supply, and plantation area. Effective supplier selection is crucial for maintaining supply chain efficiency. By employing the Expert Choice 11 software, the AHP method quantitatively assessed each criterion, resulting in a definitive ranking of suppliers. The analysis highlighted the paramount importance of quality in supplier selection, assigning it the highest weight (0.565). The outcomes reveal that a meticulous application of AHP significantly enhances decision-making in supplier selection, suggesting its broader applicability in global supply chain management contexts to improve operational efficacy and resilience. Highlights: Structured Evaluation: The AHP method provides a systematic approach to supplier assessment. Emphasis on Quality: Quality is the dominant criterion in supplier selection with the highest weight. Operational Improvement: Implementing AHP enhances supply chain efficiency and decision accuracy. Keywords: Supplier Selection, Analytical Hierarchy Process, Expert Choice